Vigilante Groups De Lege Lata and De Lege Ferenda - Flander, Benjamin (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
This paper analyses the emergence and activities of guards, village guards, and similar groups in light of applicable law, relevant constitutional jurisprudence, and proposed legislative changes. The author addresses the legal issues that arose with the appearance of the Slovene Defence Guard, particularly focusing on the public manifestation of its members and sympathizers in the capital city of Slovenia. The analysis also covers the response of the police and other authorities, civil society, and the professional public to the public rally and other activities of this and similar groups. Finding appropriate solutions for the activities of so-called anti-immigrant and other vigilante groups is a real challenge for lawmakers as well as for those responsible for upholding the legal order.